Military Lessons of the Gulf War - Watson, Bruce W. [et al.]; Edited By Brauce W. Watson (GHQ, Rawalpindi Services Book Club, 1992)
Military Lessons of the Gulf War, presents an authoritative International perspective on the military, operational and technological aspects of the Gulf War together with the political, foreign policy and stategic considerations. This unique bridge between the military and political viewpoints makes it an invaluable work of reference to set the war in the context of its time and to chart its implications for the future.
Include Index and Illustrations.
Keywords: Persian Gulf War, 1991 -- Golfkrieg (1990-1991)